Rezults of magnetic variations monitoring on the UAS «Academic Vernadskij» - Maksymcuk, V.; Klymkovych, T. (Ukrainian Antarctic Journal, 2015)
The results of magnetic variations monitoring on the UAS “Academic Vernadskij” is presented on the base of long-term (2006-2012) magnetic variations observations on the AIA Argentina Islands were developed induction vector components time series and investigated their temporal variations. Were defined anomalous changes of Vise vectors with different periods and amplitudes: annual, seasonal, diurnal and non-periodic (episodic). The nature of periodic variations is connected with an influence of external sources. Anomalous variations of Vise vectors with non-periodic changes can be depend with seismic-tectonic processes in the region.